Penicillin V acylases from gram-negative bacteria degrade N-acylhomoserine lactones and attenuate virulence in Pseudomonas aeruginosa - Sunder, Avinash Vellore; Utari, Putri Dwi; Ramasamy, Sureshkumar; van Merkerk, Ronald; Quax, Wim; Pundle, Archana (Applied Microbiology and Biotechnology, 2017)
Virulence pathways in gram-negative pathogenic bacteria are regulated by quorum sensing mechanisms, through the production and sensing of N-acylhomoserine lactone (AHL) signal molecules. Enzymatic degradation of AHLs leading to attenuation of virulence (quorum quenching) could pave the way for the development of new antibacterials. Penicillin V acylases (PVAs) belong to the Ntn hydrolase superfamily, together with AHL acylases. PVAs are exploited widely in the pharmaceutical industry, but their role in the natural physiology of their native microbes is not clearly understood. This report details the characterization of AHL degradation activity by homotetrameric PVAs from two gram-negative plant pathogenic bacteria, Pectobacterium atrosepticum (PaPVA) and Agrobacterium tumefaciens (AtPVA). Both the PVAs exhibited substrate specificity for degrading long-chain AHLs. Exogenous addition of these enzymes into Pseudomonas aeruginosa greatly diminished the production of elastase and pyocyanin and biofilm formation and increased the survival rate in an insect model of acute infection. Subtle structural differences in the PVA active site that regulate specificity for acyl chain length have been characterized, which could reflect the evolution of AHL-degrading acylases in relation to the environment of the bacteria that produce them and also provide strategies for enzyme engineering. The potential for using these enzymes as therapeutic agents in clinical applications and a few ideas about their possible significance in microbial physiology have also been discussed.
Keywords: N-acylhomoserine lactone acylase; Ntn hydrolase; pathogenesis; Penicillin Vacylase; Quorum quenching

Process development for 6-aminopenicillanic acid production using lentikats-encapsulated escherichia coli cells expressing penicillin V acylase - Sawant, Amol M.; Sunder, Avinash Vellore; Vamkudoth, Koteswara Rao; Ramasamy, Sureshkumar; Pundle, Archana (ACS Omega, 2020)
Penicillin V acylase (PVA, EC 3.5.1.11) hydrolyzes the side chain of phenoxymethylpenicillin (Pen V) and finds application in the manufacture of the pharmaceutical intermediate 6-aminopenicillanic acid (6-APA). Here, we report the scale-up of cultivation of Escherichia coli whole cells expressing a highly active PVA from Pectobacterium atrosepticum and their encapsulation in polyvinyl alcohol-poly(ethylene glycol) Lentikats hydrogels. A biocatalytic process for the hydrolysis of 2% (w/v) Pen V was set up in a 2 L reactor using the Lentikats-immobilized whole cells, with a customized setup to enable continuous downstream processing of the reaction products. The biocatalytic reaction afforded complete conversion of Pen V for 10 reaction cycles, with an overall 90% conversion up to 50 cycles. The bioprocess was further scaled up to the pilot-scale at 10 L, enabling complete conversion of Pen V to 6-APA for 10 cycles. The 6-APA and phenoxy acetic acid products were recovered from downstream processing with isolated yields of 85-90 and 87-92%, respectively. Immobilization in Lentikats beads improved the stability of the whole cells on storage, maintaining 90-100% activity and similar conversion efficiency after 3 months at 4 degrees C. The robust PVA biocatalyst can be employed in a continuous process to provide a sustainable route for bulk 6-APA production from Pen V.